The theatrical praxis and its visual roots: Sarah Kane, Maurice Maeterlinck and the Post-Dramatic - Tudella, Eduardo (2023)
This article discusses probable visual roots for theatrical praxis. I observed derivations originating in the Greek verb théa, as well as in the noun theatron, found in ancient Greece. Starting from this context, I identified theoretical links with Hans-Thies Lehmann, Peter Szondi and Ewald Hackler. Two works of international dramaturgy written at different times were incorporated into the argument, namely: Les Aveugles (1890) and 4.48 Psychosis (2000), whose authors they are, respectively, Maurice Maeterlinck (1862-1949) and Sarah Kane (1971-1999). This approach found excerpts that reveal consistent application of verbal images in the dramaturgical corpus of each of these works. Given this, I suggest academic attention to systematized studies of visual praxis in the theater.